2007
DOI: 10.1021/ie070670e
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study and Modeling of Peroxypropionic Acid Synthesis from Propionic Acid and Hydrogen Peroxide Using Homogeneous Catalysts

Abstract: This article describes a kinetic study of the perhydrolysis of propionic acid with sulfuric acid at various molar reactant ratios (PA-H2O2 from 0.4 to 2.05), reaction temperatures (from 30 to 60 °C), and catalyst concentrations (from 0 to 1.41 M). The influence of water and acidic catalysts were taken into account to develop a suitable kinetic model. The system is nonideal, mainly due to the presence of the strong electrolyte (i.e., H2SO4), and a parameter was introduced to describe the nonideality. The kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 7 publications
1
39
0
Order By: Relevance
“…Fig. 1 confirms that the perhydrolysis kinetics of propionic acid in the absence of an added catalyst is slow, but propionic acid itself is able to act as a catalyst, therefore some conversion was noticeable [6]. However, one can observe that there is a significant effect of sulfuric acid even at low concentrations (0.001 and 0.004 M), implicating that there is no clear threshold value for the added catalyst concentration.…”
Section: Influence Of Sulfuric Acid At Low Concentration On the Convesupporting
confidence: 81%
See 1 more Smart Citation
“…Fig. 1 confirms that the perhydrolysis kinetics of propionic acid in the absence of an added catalyst is slow, but propionic acid itself is able to act as a catalyst, therefore some conversion was noticeable [6]. However, one can observe that there is a significant effect of sulfuric acid even at low concentrations (0.001 and 0.004 M), implicating that there is no clear threshold value for the added catalyst concentration.…”
Section: Influence Of Sulfuric Acid At Low Concentration On the Convesupporting
confidence: 81%
“…It was decided to investigate the perhydrolysis of propionic acid; the choice of peroxypropionic acid is due to its higher stability compared to peroxyacetic acid. In a previous contribution [6], it was demonstrated that the kinetics of propionic acid perhydrolysis, catalyzed by sulfuric acid, is dependent on Brønsted concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Below this catalyst loading, the perhydrolysis of propionic acid due to the protolysis of the carboxylic acids occurs [7]. The change of the catalyst loading in the range 10.24-18.25 g/L does not influence the kinetics of H 2 O 2 decomposition at 50°C (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…This reaction occurs at acidic pH [5][6][7], and is traditionally catalyzed by sulfuric acid. This reaction was selected because spontaneous decomposition of hydrogen peroxide or peroxycarboxylic acids is negligible [8][9][10] in traditional experimental conditions (pH: 1-3; and temperature: 20-50°C); and configurational diffusion can be neglected because the size of the reactant molecules is smaller compared to the pore size of the materials used (Table 1).…”
Section: Scheme 1 Applications Of H 2 O 2 In Fine Chemical Reactionsmentioning
confidence: 99%
“…(1) [2,19,33,34]. The carboxylic acid itself can also dissociate H + , which is able to act as a catalyst to accelerate the forming rate of -COOOH [19].…”
Section: The Influence Of Functional Groups On S-removalmentioning
confidence: 99%